Flux and solder paste comprising same
By optimizing the flux composition in the solder paste, especially using components such as acidic (meth)acrylic acid copolymer and organic solvents, the problems of unstable solder paste viscosity and poor solderability in air are solved, achieving high viscosity stability stability and good welding performance.
Patent Information
- Application Number
- CN202410955965.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-07-20
- Filing Date
- 2024-07-17
- Publication Date
- 2025-01-21
AI Technical Summary
There are problems of instability in viscosity during storage and use of existing solder pastes and poor solderability when welding in air.
A flux was developed consisting of 30 to 80 wt% acidic (meth)acrylic copolymer, 10 to 60 wt% organic solvent, 0 to 15 wt% amine, and 0 wt% Composed of other components to 20% by weight, by optimizing the proportions of these components, the viscosity stability of the solder paste and the solderability in air soldering are improved.
It achieves high viscosity stability of the solder paste and good soldering ability in air, ensuring the storage stability of the solder paste and the reliability of the soldering process.
Smart Images

Figure BDA0004948778390000071 
Figure BDA0004948778390000081
Abstract
Description
[0001] The present invention relates to a flux for solder paste and a solder paste containing the flux, in particular to a solder paste for attaching an electronic component to a substrate.
[0002] Solder pastes, in particular soft solder pastes, are primarily used in the production of electronic circuits and for producing mechanical, electrical and thermal connections between electronic components and substrates, or more precisely between contact surfaces of substrates for this purpose.
[0003] Examples of electronic components within the meaning of this patent application include diodes, LEDs (light emitting diodes), dies, IGBTs (insulated gate bipolar transistors), MOSFETs (metal oxide semiconductor field effect transistors), ICs (integrated circuits), sensors, heat sinks, resistors, capacitors, coils, connecting elements (e.g., clips), base plates, antennas, etc.
[0004] Within the meaning of this patent application, examples of substrates include lead frames, PCBs (printed circuit boards), flexible electronic devices, ceramic substrates, metal ceramic substrates (such as DCB substrates (direct copper-bonded substrates)), IMS (insulated metal substrates), etc.
[0005] Electronic components are usually contacted with or applied to a substrate via solder paste. The solder paste is heated to melt the solder (solder metal, solder alloy) in the solder paste, for example, by a reflow process. After the solder cools and solidifies, the electronic component and the substrate are firmly bonded together.
[0006] In addition to solder powder, solder pastes usually contain flux. The flux serves, among other things, to dissolve oxide layers on the surface of the solder powder, the electronic components and the substrate and thus ensure better wettability during the soldering process.
[0007] The flux forming part of the solder paste is usually based on natural resins, such as rosin in particular. In addition, organic solvents, buffer bases (such as amines) and activators (such as carboxylic acids or halogen compounds) are usually contained as components in such fluxes.
[0008] The object of the present invention is to provide a solder paste having improved viscosity and thus improved storage stability and preferably also improved solderability in the presence of air, i.e. having good solderability even without having to take special measures to exclude atmospheric oxygen, such as vacuum soldering or soldering under inert gas. High viscosity stability in turn is closely related to consistent processability, such as in particular consistent printability.
[0009] The applicant was able to develop a flux that solves this problem, or more precisely a solder paste containing a flux that solves this problem. Therefore, the present invention is to provide a flux consisting of the following items:
[0010] (i) 30 to 80 wt. % (percentage by weight), preferably 35 to 70 wt. % of one or more acidic (meth)acrylic copolymers having an acid value in the range of 100 to 350 mg KOH / g and having a weight average molecular weight M in the range of 1000 to 5000 w ,
[0011] (ii) 10 to 60% by weight, preferably 20 to 50% by weight, of at least one organic solvent,
[0012] (iii) 0 to 15% by weight, preferably 4 to 12% by weight, of one or more amines,
[0013] (iv) 0 to 20 wt% of one or more components other than components (i) to (iii).
[0014] “(Meth)acrylic acid” means “methacrylic acid” and / or “acrylic acid”.
[0015] The term "acid value" as used in the present description and in the examples refers to the acid value (SZ) which can be determined in accordance with DIN EN ISO 2114 in mgKOH / g (milligrams KOH per gram).
[0016] Unless otherwise stated, all standards cited in the specification and examples are in the version current at the priority date of this patent application.
[0017] The weight average molecular weight M mentioned in this specification and in the examples is w The determination can be carried out in a customary manner known to the person skilled in the art by means of GPC, for example in accordance with DIN 55672-1 (March 2016, crosslinked polystyrene as stationary phase, tetrahydrofuran as liquid phase, polystyrene standards, 23° C.).
[0018] Depending on the presence of components (iii) and / or (iv), the flux may therefore consist of components (i) plus (ii) or (i) plus (ii) plus (iii) or (i) plus (ii) plus (iv) or (i) plus (ii) plus (iii) plus (iv), and in each of these alternatives the sum of the weight % of the respective components is 100 weight %.
[0019] As component (i), the flux according to the invention comprises 30 to 80 wt. %, preferably 35 to 70 wt. % of one or more different acidic (meth) acrylic copolymers. Preferably, it is only one acidic (meth) acrylic copolymer. The acidic (meth) acrylic copolymer has an acid number in the range of 100 mg KOH / g to 350 mg KOH / g, preferably 150 mg KOH / g to 300 mg KOH / g. The one or more acidic (meth) acrylic copolymers have a weight average molecular weight M in the range of 1000 to 5000, preferably in the range of 1000 to 3000, and in particular in the range of 1500 to 2500. w . Having an acid value in the range of 150 mg KOH / g to 300 mg KOH / g and a weight average molecular weight M in the range of 1000 to 3000 or 1500 to 2500 w Acidic (meth) acrylic copolymers are preferred. These are copolymers of (meth) acrylic compounds that can be prepared by free radical copolymerization in a conventional manner known to those skilled in the art, and the copolymers may also contain comonomers different from those of the (meth) acrylic acid type, such as vinyl compounds and / or other ethylenically unsaturated free radical copolymerizable compounds, in a total proportion by weight of <50 wt % based on the total acidic (meth) acrylic copolymer. Examples of (meth) acrylic compounds that account for >50 wt % based on the total (meth) acrylic copolymer are (meth) acrylic acid, (meth) acrylic esters and (meth) acrylamide. Examples of vinyl compounds include compounds such as vinyl esters, vinyl ethers, styrene, etc.
[0020] Preferably, the acidic (meth)acrylic copolymer has a glass transition temperature (T g ). The glass transition temperature can be determined using dynamic differential scanning calorimetry (DSC) based on DIN 51007 at a heating rate of 10 K / min.
[0021] Acidic (meth)acrylic acid copolymers of the abovementioned type are commercially available. Examples thereof are the products labeled Indurez from IndudorChemie GmbH and the products labeled TUNE from BASF. Products found.
[0022] As component (ii), the flux according to the invention comprises 10 to 60% by weight, preferably 20 to 50% by weight, of at least one organic solvent. Examples include diols, alcohols, ether alcohols and ketones which are liquid at 25° C., in particular trimethylpropanol, 1,2-octanediol, 1,8-octanediol, 2,5-dimethyl-2,5-hexanediol, isobornylcyclohexanol, glycol ethers, 2-ethyl-1,3-hexanediol, n-decanol, 2-methyl-2,4-pentanediol, terpineol and isopropanol and mixtures thereof. Examples of glycol ethers include monopropylene glycol methyl ether, dipropylene glycol methyl ether, tripropylene glycol methyl ether, monopropylene glycol n-butyl ether, dipropylene glycol n-butyl ether, tripropylene glycol n-butyl ether, monoethylene glycol n-butyl ether, diethylene glycol n-butyl ether, triethylene glycol n-butyl ether, ethylene glycol dimethyl ether, triethylene glycol methyl ether, diethylene glycol dibutyl ether, tetraethylene glycol dimethyl ether and diethylene glycol monohexyl ether and mixtures thereof.
[0023] As component (iii), the flux according to the invention comprises 0 to 15 wt. %, preferably 4 to 12 wt. % of one or more amines, i.e. the flux according to the invention may comprise one or more amines or be free of amines, preferably comprises one or more amines. Examples of amines include N,N,N',N'-tetramethylethylenediamine, N,N,N',N'-tetraethylethylenediamine, N,N,N',N'-tetrapropylethylenediamine, N-cocoyl-1,3-diaminopropane, 1,6-diaminohexane, 1,7-diaminoheptane, 1,8-diaminooctane, 1,9-diaminononane and 1,10-diaminodecane, bis(2-ethylhexyl)amine, bis(2-methylhexyl)amine, diethylamine, triethylamine, cyclohexylamine, diethanolamine, triethanolamine, hydrogenated tallow alkylamines, hydrogenated (tallow alkyl)dimethylamine and hydrogenated bis(tallow alkyl)methylamine.
[0024] As component (iv), the flux according to the invention comprises 0 to 20% by weight of one or more components different from components (i) to (iii), i.e. the flux according to the invention may comprise one or more components of type (iv) or be free of these components. Examples of ingredients of type (iv) include in particular thickeners, but also activators, defoamers, wetting aids and / or stabilizers.
[0025] Examples of thickeners include ethylcellulose, hydrogenated castor oil, glyceryl tri-12 hydroxystearate, and modified glyceryl tri-12 hydroxystearate.
[0026] Examples of low molecular weight carboxylic acids which can be used as activators include benzilic acid, oxalic acid, adipic acid, malonic acid, succinic acid, glutaric acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecanedioic acid and tridecanedioic acid. It may be advantageous if the flux according to the invention comprises from 2% to 15% by weight of at least one low molecular weight carboxylic acid as a type (iv) component; in the case of such an embodiment, the flux according to the invention may correspondingly comprise a maximum of 5% to 18% by weight of other type (iv) components, but other than low molecular weight carboxylic acids.
[0027] Examples of the halogen-containing compound that can be used as the activating agent include aniline hydrochloride, glutamic acid hydrochloride, diethanolamine hydrochloride, diethanolamine hydrobromide, triethanolamine hydrochloride, triethanolamine hydrobromide, and trans-2,3-dibromo-2-butene-1,4-diol.
[0028] Preferably, the flux according to the invention, i.e. the entire flux consisting of components (i) plus (ii) or (i) plus (ii) plus (iii) or (i) plus (ii) plus (iv) or (i) plus (ii) plus (iii) plus (iv), has a flux acid value (FMSZ) in the range of 100 mg KOH / g to 250 mg KOH / g, preferably in the range of 120 mg KOH / g to 220 mg KOH / g. The flux acid value mentioned in the present description and in the examples can be determined according to IPC TM-650 2.3.13 (dated June 2004, Revision A). The flux acid value is at least substantially or completely formed by the carboxyl groups of component (i) and optionally the carboxyl groups contributed by component (iv).
[0029] The present invention also includes a solder paste comprising 80% to 92% by weight of one or more different solders and 8% to 20% by weight of a flux according to the present invention, i.e., a flux according to the present invention in one of the aforementioned embodiments thereof. The sum of the weight percentages of the solder and the weight percentages of the flux according to the present invention is 100% by weight.
[0030] As described above, the solder paste according to the invention contains 80 to 92 wt. % of one or more different solders, in particular a solder based on tin (a solder alloy containing at least 80 wt. %, preferably at least 83 wt. %, in particular 90 to 99.5 wt. % tin) or based on bismuth / tin (a solder alloy containing 50 to 60 wt. % bismuth and 40 to 50 wt. % tin).
[0031] Preferably, the solder has a liquidus temperature in the range of 150°C to 350°C, preferably in the range of 180°C to 300°C.
[0032] One or more solders are present in the solder paste according to the present invention in the form of solder powder, as is usually used for solder pastes. The ball size of the solder balls constituting the solder powder may correspond to any classification according to the IPC J-STD-005A standard, i.e. the solder paste according to the present invention may have solder balls of any type of ball size within the type range T1 to T7.
[0033] Preferably, the solder paste according to the invention has a viscosity of 50 Pa·s to 250 Pa·s. The viscosities mentioned in the present description and in the examples can be measured using a plate-plate rheometer (e.g. a plate-plate rheometer Physica MCR 150 from Anton-Paar) at 25° C. and 10 s -1 Measured at a shear rate of .
[0034] A further object of the invention is a method for producing a solder paste according to the invention.
[0035] The method for producing the solder paste according to the present invention comprises the following steps:
[0036] - mixing the components of the flux according to the invention; and
[0037] -Add solder powder as described above.
[0038] The solder powder is usually added in portions to the prepared mixture of the components of the flux according to the invention without heating, preferably while stirring.
[0039] The solder paste according to the invention can be used to connect electronic components to substrates. It can also be used to produce solder deposits on substrates.
[0040] When the electronic component is connected to the substrate, the contact surface of the substrate and the contact surface of the electronic component are bonded via the solder paste according to the present invention.
[0041] A method for attaching an electronic component to a substrate using the solder paste according to the present invention may include the following steps:
[0042] a) providing an electronic component having a contact surface,
[0043] b) providing a substrate having a contact surface,
[0044] c) applying solder paste to the contact surface of the electronic component and / or the contact surface of the substrate,
[0045] d) bonding the contact surface of the electronic component to the contact surface of the substrate using solder paste; and
[0046] e) The solder paste is heated to above the liquidus temperature of the solder, and the solder is then allowed to cool and solidify, forming a tight bond between the electronic component and the substrate.
[0047] Steps a) and b) are self-explanatory and require no further explanation.
[0048] In step c), the solder paste according to the invention can be applied to one or both contact surfaces by means of conventional methods known to the person skilled in the art, for example by means of screen printing or stencil printing or dispensing or spraying.
[0049] In step d), the contact surfaces of the electronic component and the substrate may be bonded together using a solder paste. In other words, a sandwich arrangement may be created from the electronic component and the substrate with the solder paste between their contact surfaces.
[0050] In step e), the sandwich assembly can be soldered by heating the solder paste to a temperature above the liquidus temperature of the solder, so that a tight connection is formed between the electronic component and the substrate via the solder paste after the solder cools and solidifies. The solder paste is preferably heated in such a way that the solder enters its liquid phase, but does not damage the electronic component and / or the substrate. The sandwich assembly or more precisely the solder paste is preferably heated to a temperature above the liquidus temperature of the solder, in the range of 5°C to 60°C, preferably 10°C to 50°C.
[0051] Advantageously, a solder paste comprising the flux according to the invention allows soldering to be performed in air according to step e) independently of the ball size of the solder powder used in the solder paste. Example
[0052] Preparation of flux and solder paste
[0053] The components of the flux were combined according to Table 1 and homogenized.
[0054] To prepare the solder paste, 11 parts by weight of flux was mixed with 89 parts by weight of solder powder (SnAgCu: Sn 96.5 wt %, Ag 3.0 wt %, Cu 0.5 wt %, Type 4 according to IPC J-STD-005A standard) to form the solder paste.
[0055] Wetting ability under normal atmospheric conditions
[0056] The wetting properties of the solder paste were evaluated under normal atmospheric conditions using the fusion test according to IPC-TM-650 (1 / 95) test method 2.4.45. For this purpose, the solder paste to be tested was applied to a copper sheet (20 mm x 20 mm x 0.5 mm). If the copper sheet had an oxide layer on the surface, it was ground to a bright metal surface with P600 fine-grain sandpaper and cleaned with ethanol. Copper sheets with a bright and clean surface were cleaned only with ethanol.
[0057] The prepared copper sheet is printed using a stencil. To do this, the stencil is pressed firmly against the copper sheet so that the opening in the stencil is in the middle of the copper sheet. The solder paste to be tested is placed on a Japanese spatula and spread over the opening of the stencil, first gently and then with slightly greater pressure, until there is no more solder paste on the stencil. The stencil is then carefully removed while retaining the pattern defined by the stencil. The printed copper sheet is placed on a first 200°C hot hot plate set to a temperature below the liquidus temperature of the solder for 2 minutes, and then immediately placed on a second hot plate set to a temperature 50°C above the liquidus temperature of the solder. After the solder paste or solder has melted, the copper sheet is placed on the second hot plate for another 5 seconds, and then removed and cooled.
[0058] After the solder paste had cooled, it was evaluated whether it had melted into a spot corresponding to the size of the opening in the stencil or into multiple small spots, and whether the solder paste had sharp edges after melting. It was also evaluated whether the surface was shiny or matte.
[0059] Solder pastes are divided into four categories:
[0060] Category 1: The remelted area is larger than the area previously printed with solder paste.
[0061] Class 2: The remelted area corresponds to the surface previously printed with solder paste.
[0062] Category 3: The remelted area is smaller than the area previously printed with solder paste (slight dewetting can be seen).
[0063] Category 4: The solder paste has formed one or more solder balls and has not wetted the copper or has not completely melted.
[0064] Viscosity stability test at room temperature
[0065] First, a plate-plate rheometer (Physica MCR 150 from Anton Paar; plate diameter 50 mm, measuring gap 400 μm) was used at 25° C. and 10 s. -1 The initial viscosity of the freshly prepared solder pastes was determined at a shear rate of 1.5 %. The solder pastes were then each stored in a sealed container at room temperature (23° C.) and measured again after seven days, as described above. Before measuring the viscosity after seven days of storage, each type of solder paste was simply mixed homogeneously by hand with a spatula. The difference between the first measured value recorded directly after the preparation of the relevant solder paste and the second measured value recorded in each case after the relevant solder paste had been stored for seven days was evaluated as follows:
[0066] ++: <5Pa·s
[0067] +: 5Pa·s to <10Pa·s
[0068] -:>10Pa·s
[0069] Table 1: Composition and measurements of fluxes 1 to 3 according to the invention and comparative fluxes V1 and V2 result
[0070]
[0071]
Claims
1. A flux, the flux consisting of the following items: (i) 30 to 80 wt% of one or more acidic (meth)acrylic copolymers having an acid value in the range of 100 to 350 mg KOH / g and having a weight average molecular weight M in the range of 1000 to 5000 w , (ii) 10% to 60% by weight of at least one organic solvent, (iii) 0% to 15% by weight of one or more amines, and (iv) 0 to 20 wt% of one or more components other than components (i) to (iii).
2. The flux according to claim 1, wherein the acid value is in the range of 150 mg KOH / g to 300 mg KOH / g and the weight average molecular weight M w In the range of 1000 to 3000.
3. The flux according to claim 1 or 2, wherein the acidic (meth) acrylic copolymer has a glass transition temperature (Tg) in the range of >0°C to ≤105°C. g ).
4. The flux according to any one of the preceding claims, wherein the flux has a flux acid value (FMSZ) in the range of 100 mg KOH / g to 250 mg KOH / g.
5. A solder paste consisting of 80 to 92% by weight of one or more different solders and 8 to 20% by weight of the flux according to one of claims 1 to 4.
6. Use of a solder paste according to claim 5 for connecting an electronic component to a substrate or for producing a solder deposit on a substrate.